The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13039-018-0355-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the proneural transcription factor ASCL1 in chronic lymphocytic leukemia with a t(12;14)(q23.2;q32.3)

Abstract: BackgroundTranslocations of the IGH locus on 14q32.3 are present in about 8% of patients with chronic lymphocytic leukemia (CLL) and contribute to leukemogenesis by deregulating the expression of the IGH-partner genes. Identification of these genes and investigation of the downstream effects of their deregulation can reveal disease-causing mechanisms.Case presentationWe report on the molecular characterization of a novel t(12;14)(q23.2;q32.3) in CLL. As a consequence of the rearrangement ASCL1 was brought into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In addition, a case study reported nuclear translocation t(12; 14) (q23.2; Q32.3) may make ASCL bind to INSM1 enhancer, upregulating INSM1 expression in chronic lymphocytic leukemia. This also leads us to explore the possibility of “reexpression” of INSM1 in blood diseases [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a case study reported nuclear translocation t(12; 14) (q23.2; Q32.3) may make ASCL bind to INSM1 enhancer, upregulating INSM1 expression in chronic lymphocytic leukemia. This also leads us to explore the possibility of “reexpression” of INSM1 in blood diseases [ 27 ].…”
Section: Introductionmentioning
confidence: 99%